Dynamic fault tree analysis approach to Safety Analysis of Civil Aircraft - Qichuan Geng; Haibin Duan; Shuangtian Li (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
As one of key projects of China at present, the safety of the civil aircraft is a major issue first considered in design and development. Fault-tolerant systems with redundancy are used more often for the design of modern advanced large aircraft. It is a new research area for the safety analysis technology which is not perfect in China. A novel approach to Safety Analysis of Civil Aircraft based on Dynamic Fault Tree Analysis has been proposed in this paper. This paper takes the mature typical design of large aircraft and general aircraft in developed countries as research object, performs safety analysis using dynamic fault tree, and optimizes the analysis of fault tree using modularization thinking. Then, the failure probability of civil aircraft can be calculated in the newly-developed simulation software.